Integration of Science and Religion in Islamic Education: A Bibliometric and Network Visualization Study - Mohammad Nahrawi; Benny Prasetiya; Febry Suprapto; Khoiriyah (Immortalis Journal of Interdisciplinary Studies, 2026)
This study comprehensively examines the global dynamics of research on the integration of science and religion within the framework of Islamic education through a bibliometric and network visualization approach using data from Scopus and the Web of Science (WoS). Utilizing VOSviewer software, the study systematically maps the scientific landscape encompassing publication trends, intellectual structures, and thematic interconnections among key concepts that shape the discourse on Islam–science–education. The analysis reveals a significant increase in scholarly output over the past two decades, with a sharp surge after 2010 and a peak in publication activity between 2019 and 2021. Indonesia ranks as the leading contributor, followed by the United States, Iran, Turkey, and Malaysia, reflecting a geographical shift in the center of Islamic educational research toward Asia and the Middle East. The dominance of the social sciences (36.7%) and humanities (28.5%) indicates an epistemological transformation from a normative theological paradigm toward an interdisciplinary framework that integrates scientific rationality with spiritual values. Four major thematic clusters religion–Islam–education, human–article–humans, cultural anthropology–history, and higher education engineering education represent interconnected domains that converge toward strengthening the Tawhidic Epistemology and Integrative Knowledge Theory, emphasizing the holistic unity between knowledge, spirituality, and humanity. The principal novelty of this study lies in the conceptualization of the Humanized Islamic Knowledge System (HIKS), an epistemological synthesis uniting faith, reason, and scientific inquiry within an ethical and humanistic framework. This paradigm introduces two key constructs Techno-Ethical Islamic Education and Scientific-Spiritual Synthesis positioning Islamic education as the moral compass of the 21st century, guiding the advancement of science and technology toward an ethical, inclusive, and spiritually transformative civilization.